Prebiotic effects of yacon (Smallanthus sonchifolius Poepp. & Endl), a source of fructooligosaccharides and phenolic compounds with antioxidant activity - Campos D. (2012)
The authors thank Marco Ibarra-Castro, Ana Carrasco and Adelayda Pardo for their technical assistance. Dr. Carlos Arbizu from the International Potato Center (CIP), Lima - Perú, is kindly acknowledged for provision of the 35 yacon accessions. This work was supported by the Consejo Nacional de Ciencia y Tecnología (CONCYTEC), Perú.